International Co-movements of Inflation, 1851-1913 - Stefan Gerlach; Rebecca Stuart (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
We study co-movements of inflation in a group of 15 countries before and during the classical Gold Standard by fitting a generalisation of the Ciccarelli-Mojon (2010) model on annual data spanning 1851-1913. We find that international inflation functions as an "attractor" for domestic inflation rates. The cross-sectional dispersion of inflation declined gradually over the sample and Bai-Perron tests for structural breaks at unknown points in time suggest that there are breaks in six of reduced-form inflation equations. However, sub-sample estimates indicate that the overall finding that international inflation is an important influence on domestic inflation.
Keywords: E31; F40; N10; 330; international inflation; Gold standard; principal components; factor analysis